Right atrial structure and function in patients with hypertension and with chronic heart failure. Issue 7 (30th March 2018) - Proplesch, Moritz; Merz, Allison A.; Claggett, Brian L.; Lewis, Eldrin F.; Dwyer, Kristin H.; Crousillat, Daniela R.; Lau, Emily S.; Silverman, Montane B.; Peck, Julie; Rivero, Jose; Cheng, Susan; Platz, Elke
Abstract : Background: Prior studies have shown that both heart failure (HF) and atrial fibrillation (AF) are factors that impact left atrial function and structure. However, right atrial (RA) function measured as RA emptying fraction (RAEF) on echocardiography has not been analyzed systematically in a chronic HF population. The aim of this study was to assess RA volume index (RAVI) and RAEF in patients with chronic HF and patients with hypertension (HTN) and to relate these findings to other cardiopulmonary ultrasound parameters and 12‐month outcomes. Methods and Results: In this prospective observational study, we identified 119 patients with chronic HF (64 patients without a history of AF [HF without AF], 55 with AF [HF with AF]), and 127 patients with HTN but without important cardiac disease who underwent routine outpatient transthoracic echocardiography. We found that RAEF was impaired in patients with HF without AF compared to patients with HTN (35% ±2 vs 50% ±1, P  < .001), whereas RAVI did not differ between these two groups. Lower RAEF was associated with larger RAVI and higher estimated RA pressures but not with a higher degree of pulmonary congestion by lung ultrasound. Both lower RAEF and higher RAVI were associated with an increased risk of 12‐month HF hospitalizations or all‐cause death (age, sex, and AF adjusted HR: 4.07, 95% CI: 1.69–9.79; P  = .002, vs 2.74, 95% CI: 1.15–6.54, P  = .023). Conclusions: In an outpatient HF cohort, both lower RAEF and increased RAVI were associated with other markers of impaired cardiac function and 12‐month adverse events.